2002
DOI: 10.1889/1.1830143
|View full text |Cite
|
Sign up to set email alerts
|

39.3: Development of a Low Temperature Process of Ballistic Electron Surface‐Emitting Display (BSD) on a Glass Substrate

Abstract: Ballistic electron Surface-emitting Display (BSD) is successfully fabricated on a glass substrate with low temperature process. 168 (RGB) x 126 pixels, 2.6 inches diagonal full-colour BSD exhibits excellent performance as a flat panel display. Main fabrication process is an anodisation and subsequent electrochemical oxidation process at a low temperature, which will contribute to larger panel size and process-cost reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…The NPS layers are formed by conventional anodization ͑at 10 mA/cm 2 for 10 s in an ethanoic HF solution at 7°C) and subsequent electrochemical oxidation ͑ECO͒ by anodization in an H 2 SO 4 solution ͑at a current density of 10 mA/cm 2 for 60 s͒ as reported previously. 4,5 As a next step, post-ECO annealing process at a temperature of 550°C in a gas atmosphere of N 2 ϩ3%H 2 for 1 h is employed in order to remove H 2 O molecules 8 and hydrogen related species 9 that possibly degrade dielectric property of ECO-formed SiO 2 films. 10 Finally thin-film top electrodes composed of an 8-nm-thick Au layer on a 2-nm-thick Cr layer are formed on the NPS layer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NPS layers are formed by conventional anodization ͑at 10 mA/cm 2 for 10 s in an ethanoic HF solution at 7°C) and subsequent electrochemical oxidation ͑ECO͒ by anodization in an H 2 SO 4 solution ͑at a current density of 10 mA/cm 2 for 60 s͒ as reported previously. 4,5 As a next step, post-ECO annealing process at a temperature of 550°C in a gas atmosphere of N 2 ϩ3%H 2 for 1 h is employed in order to remove H 2 O molecules 8 and hydrogen related species 9 that possibly degrade dielectric property of ECO-formed SiO 2 films. 10 Finally thin-film top electrodes composed of an 8-nm-thick Au layer on a 2-nm-thick Cr layer are formed on the NPS layer.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The cold cathode, termed ballistic electron surface-emitting device ͑BSD͒, has been fabricated on glass substrates using polysilicon films for application to a flat panel display. 4,5 To clarify the ballistic emission mechanism and to improve the emission characteristics further, it is important to investigate the emission characteristics in relation to nanostructure in anodized poly-Si films including the interfacial oxides. Based on our previous optical analyses of anodized nc-Si samples in terms of photoluminescence ͑PL͒, 6,7 direct observation of the nanostrucutre has been pursued by highresolution field effect transmission electron microscope ͑FE-TEM͒.…”
Section: Introductionmentioning
confidence: 99%
“…Using thermal or chemical oxidation, PSi can be either partially or fully oxidized depending on temperature, initial porosity, and treatment duration [4,68], whereas electrochemical oxidation is limited by the electrical contact between the substrate and the PSi layer, which deteriorate upon oxidation [69][70][71][72][73][74]. However, the latter technique provides a high control over the extent of oxidation and resulting nanostructure and was used in various PSi devices [75][76][77].…”
Section: Oxidation Of Porous Simentioning
confidence: 99%
“…A prototype of 4 Â 4 pixels display panel was demonstrated [135,136]. Another prototype was fabricated on a glass substrate using a low-temperature process (oxidation was performed electrochemically) [77]. This flat panel display was 168 Â 126 pixels, 2.6 in.…”
Section: Sensing Based On Change Of Conductivitymentioning
confidence: 99%
“…6 We also developed a low-temperature process to fabricate the BSD on a TFT and PDP glass substrate. 7 An electrochemical oxidation (ECO) technique was one of the key process concept to reduce process temperature. It was also shown that the BSD had excellent thermal stability and a frit sealed model was fabricated.…”
Section: Introductionmentioning
confidence: 99%